Sesamoid disease in two dogs - KARKANIS, A. F.; PRASSINOS, N. N.; KAZAKOS, G.; KTORIS, M.; ANTONOPOULOS, K.; KRYSTALLI, N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Two young dogs, a Rottweiler and an Épagneul Breton, presented with chronic forelimb lameness. Orthopaedic examination confirmed the mild lameness and revealed pain on deep palpation at the palmar aspect of the 5th metacarpal. Radiographic evaluation revealed fracture of the 7th metacarpophalangeal sesamoid at the 5th metacarpophalangeal joint. Based on these findings, diagnosis of sesamoid disease was achieved. Both cases had been treated conservatively with restricted activity and anti-inflammatory drugs without any success. Then, resection of the affected sesamoid was performed. The outcome was good and the dogs were free of lameness 1 year post-operatively.